TVT ABBREVO: cadaveric study of tape position in foramen obturatum and adductor region - Hubka, Petr; Nanka, Ondrej; Masata, Jaromir; Martan, Alois; Svabik, Kamil (International urogynecology journal, 2016)
INTRODUCTION AND HYPOTHESIS: The aim of the study was to describe fixation of the TVT ABBREVO and establish whether the tape penetrates through obturator muscles and membrane (obturator complex) into the adductor region and, if so, how far it penetrates. METHODS: Eight formalin-embalmed female cadavers were used to simulate TVT ABBREVO surgery (totalling 16 insertions). Following tape insertion, dissection was performed and ends of the tape were identified. In cases of penetration, the length of tape penetrating into the adductor region was measured. RESULTS: Of the 16 cases, the tape ended in the obturator membrane in eight, in the internal obturator muscle in one, and penetrated through the obturator membrane into the external obturator muscle in five, where it remained. In two cases, it penetrated through the obturator internus muscle, obturator membrane and obturator externus muscle into the group of thigh adductors; one penetration was by 3 mm and the second by 10 mm. No contact with the obturator nerve or its branches was noted in any case. CONCLUSIONS: No TVT contact with the obturator nerve was noted; tape penetrated into the adductor region in two of the 16 cases.
Keywords: Anatomy; kosterní svaly; Gynecologic Surgical Procedures; TVT ABBREVO; suburetrální pásky; Muscle, Skeletal; Complications; lidé; Female; Suburethral Slings; ženské pohlaví; gynekologické chirurgické výkony; Sling fixation; Humans; Cadaver study; Urogynecology